2005
DOI: 10.1111/j.1399-3011.2005.00261.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of geranylazide and farnesylazide diphosphate for incorporation of prenylazides into a CAAX box‐containing peptide using protein farnesyltransferase*

Abstract: Protein farnesyltransferase (PFTase) catalyzes the attachment of a geranylazide (C10) or farnesylazide (C15) moiety from the corresponding prenyldiphosphates to a model peptide substrate, N-dansyl-Gly-Cys-Val-Ile-Ala-OH. The rates of incorporation for these two substrate analogs are comparable and approximately twofold lower than that using the natural substrate farnesyl diphosphate (FPP). Reaction of N-dansyl-Gly-Cys(S-farnesylazide)-Val-Ile-Ala-OH with 2-diphenylphosphanylbenzoic acid methyl ester then gives… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
36
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 22 publications
1
36
0
2
Order By: Relevance
“…The short synthesis involved low‐temperature acid‐catalyzed selenium dioxide oxidation of 10 14 and diphosphorylation of the resulting chloride 11 15 (Tables S1, S2 and Figures S13–S16). For 1 H NMR and GC–MS comparison, an authentic sample of aldehyde 4 was prepared from commercially available (11 R )‐dihydroartemisinic acid (11 R )‐ 6 (Figures S7, S8, S26, S27) 6b, 16…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The short synthesis involved low‐temperature acid‐catalyzed selenium dioxide oxidation of 10 14 and diphosphorylation of the resulting chloride 11 15 (Tables S1, S2 and Figures S13–S16). For 1 H NMR and GC–MS comparison, an authentic sample of aldehyde 4 was prepared from commercially available (11 R )‐dihydroartemisinic acid (11 R )‐ 6 (Figures S7, S8, S26, S27) 6b, 16…”
mentioning
confidence: 99%
“…To further investigate the capability of ADS to act on unnatural substrates, 12‐acetoxyfarnesyl diphosphate ( 13 ) was prepared in three steps (32 % overall yield) from known 1‐ O ‐THP‐protected 12‐hydroxyfarnesol14 (Figures S17, S18) and incubated with ADS. GC–MS analysis revealed that the same three products were obtained as from incubations with diphosphate 7 (Figure 2 and Figure S9).…”
mentioning
confidence: 99%
“…Later, the authors used a biotin-geranylgeranyl (GerGer) pyrophosphate analog and an engineered protein prenyltransferases to analyse the in vivo effects of protein prenyltransferase inhibitors by quantifying by MS the amount of biotin-GerGer-tagged RabGTPases after treatment with inhibitors [115]. Synthesis of additional farnesyl diphosphate analogs bearing alkyne or azide groups [116,117] as well as in vitro studies to characterize them as substrates for the corresponding prenyl transferases have also been described by other groups [118,119]. Recently, Tate and co-workers reported an azido-derived GerGer pyrophosphate that could serve as a substrate for both GGTase I and RabGGTase and be subsequently modified by CuAAC to incorporate a double labeled tag [120].…”
Section: Staudinger Ligationmentioning
confidence: 99%
“…Die kurze Synthese erforderte eine SelendioxidOxidation von 10 [14] bei niedriger Te mperatur mit tBuOOH und eine Diphosphorylierung des entstandenen Chlorids 11 [15] (siehe die Tabellen S1, S2 und S13-S16). Fürd en 1 H-NMRund GC-MS-Vergleich wurde eine authentische Probe des Aldehyds 4 aus handelsüblicher (11R)-Dihydroartemisinsäu-re (11R)-6 hergestellt (siehe Abbildungen S7, S8, S26, S27).…”
unclassified
“…Fürd en 1 H-NMRund GC-MS-Vergleich wurde eine authentische Probe des Aldehyds 4 aus handelsüblicher (11R)-Dihydroartemisinsäu-re (11R)-6 hergestellt (siehe Abbildungen S7, S8, S26, S27). Um die Fähigkeit von ADS zur Umsetzung nichtnatürli-cher Substrate weiter zu untersuchen, wurde 12-Acetoxyfarnesyldiphosphat (13)i nd rei Schritten (32 %G esamtausbeute) aus dem bekannten 1-O-THP-geschützten 12-Hydroxyfarnesol [14] hergestellt (siehe die Abbildungen S17, S18) und mit ADS inkubiert. Die GC-MS-Analyse ergab,dass die gleichen drei Produkte wie durch Inkubation mit Diphosphat 7 erhalten wurden (siehe Abbildung 2u nd Abbildung S9).…”
unclassified